Dynamics and Timing of in Vivo Mutations at Gag Residue 242 during Primary HIV-1 Subtype C Infection - Novitsky, Vladimir (2010)
Viral mutations at Gag residue 242 and relevant viral polymorphisms were analyzed in a cohort of 42 individuals with primary HIV-1 subtype C infection using single-genome amplification/sequencing. In HLA-B*57/5801-negative subjects infected with 242N escape variant, reversion to Asn appeared at median (IQR) 103 (97;213) days post-seroconversion (p/s), and became dominant at 193 (170;215) days p/s. In subjects expressing HLA-B*57/5801 and infected with the wild type virus, the T242N escape appeared at 203 (196;231) days p/s, reached dominance at 277 (265;315) days p/s, and became complete at 323 (289;373) days p/s. HLA-B*57/5801-negative subjects infected with 242N escape variant did not show reduced viral load or increased CD4 count. The study highlights differential selection of T242N escape by HLA-B*57 and B*5801, and suggests the presence HLA-B*57/5801-mediated immune pressure is able to control replication of the wild type virus encoding Thr at Gag residue 242, but fails to suppress the T242N escape variant.